English for Academic Purposes Related to Dentistry: Analyzing the Reading Comprehension Process - Patricia Carabelli (Universidad Nacional de Colombia, 2021)
The Universidad de la República, in Uruguay, offers reading comprehension in English courses within the career of dentistry for students to access information in this language. The study sought to analyze the fulfilment of the course's aims and to test the hypothesis that the greater the vocabulary that dentistry students possess, the better they will be able to understand written dentistry texts. A mixed approach, based on interviews and a class survey, was used. Data showed that the course's objectives were achieved. Participants stated that the course is highly meaningful, and they believed that the previously mentioned correlation exists. However, this could not be statistically verified, which indicates that multiple reading comprehension skills are involved when trying to understand academic texts.